Evaluation of Behavior and Survival of Fish Exposed to an Axial‐Flow Hydrokinetic Turbine. (6th February 2015) - Amaral, Stephen V.; Bevelhimer, Mark S.; Čada, Glenn F.; Giza, Daniel J.; Jacobson, Paul T.; McMahon, Brian J.; Pracheil, Brenda M.
Abstract: Previous studies have evaluated fish injury and mortality at hydrokinetic (HK) turbines, but because these studies focused on the impacts of these turbines in situ they were unable to evaluate fish responses to controlled environmental characteristics (e.g., current velocity and light or dark conditions). In this study, we used juvenile hybrid Striped Bass (HSB; Striped Bass Morone saxatilis × White Bass M. chrysops ; N = 620), Rainbow Trout Oncorhynchus mykiss ( N = 3, 719), and White Sturgeon Acipenser transmontanus ( N = 294) in a series of laboratory experiments to (1) evaluate the ability of fish to avoid entrainment through an axial‐flow HK turbine, (2) evaluate fish injury and survival associated with turbine entrainment, and (3) compare the effects of different HK turbines on fish. We found that the probability of turbine entrainment was species dependent and highest for HSB. Across species, current velocity influenced entrainment probability. Among entrained fish, observed survival rates were generally >0.95. The probability of injury for surviving entrained fish only differed from that for nonentrained fish for Rainbow Trout and in general was not >0.20. The probability of injury following entrainment was greater only for HSB, although there were no differences in injury rates between fish that were turbine entrained and those that were not, suggesting that injuries were not turbine related. Taking turbine entrainment, survival, and injury estimates together allowed us to estimate the probability of a randomly selected fish in a population proximate to an HK turbine surviving passage or remaining uninjured after passage. For species and current velocities for which there was a significant effect due to entrainment, we estimated, for instance, that HSB had a survival probability of 0.95 and that Rainbow Trout and White Sturgeon had a >0.99 probability of survival. Similarly, by combining these estimates with those from previous studies, we derived total passage survival probabilities >0.90 but generally approaching 1.00 across different HK turbine types, fish species, and fish lengths. Received May 14, 2014; accepted October 23, 2014